Changes in Lipoprotein Particles in the Blood Serum of Patients with Lichen Planus - Liis Ilves; Aigar Ottas; Liisi Raam; Mihkel Zilmer; Tanel Traks; Viljar Jaks; Külli Kingo (Metabolites, 2023)
Lichen planus is a chronic inflammatory mucocutaneous disease that belongs to the group of papulosquamous skin diseases among diseases like psoriasis, a widely studied disease in dermatology. The aim of the study was to identify the changes between the blood sera of lichen planus patients and healthy controls to widen the knowledge about the metabolomic aspect of lichen planus and gain a better understanding about the pathophysiology of the disease. We used high-throughput nuclear magnetic resonance (NMR) spectroscopy to measure the levels of blood serum metabolites, lipoproteins and lipoprotein particles. Dyslipidemia has relatively recently been shown to be one of the comorbidities of lichen planus, but the changes in the components of lipoproteins have not been described yet. We found statistically significant changes in the concentrations of 16 markers regarding lipoproteins, which included the components of intermediate-density lipoproteins, low-density lipoproteins and large low-density lipoproteins. We propose that the detected changes may increase the risk for specific comorbidities (e.g., dyslipidemia) and resulting cardiovascular diseases, as the turnover and hepatic uptake of the altered/modified lipoprotein particles are disturbed.